Characteristics of menstrual cycle disorder and saliva metabolomics of young women in a high-temperature environment - Wei, MengFan; An, GaiHong; Fan, LiJun; Chen, XueWei; Li, Chao; Chen, JiaJun; Ma, Qiang; Yang, DanFeng; Wang, Jing (Frontiers in Physiology, 2023)
Objective: Menstrual disorders induced by high-temperature environments, can seriously damage women’s reproductive health and workability. The regulation mechanism underlying it is not yet to be elucidated. Saliva is an information-rich biological fluid that can reflect systemic diseases. Here, we investigated the characteristics of menstrual cycle disorders and saliva metabolomics to provide a deeper insight of the regulation mechanism of young women in high-temperature environments. Methods: Women from high and normal temperature areas of China were selected and divided into two groups—high-temperature (H group) and control (C group). A questionnaire survey was conducted in summer (July) to investigate the incidence rate of menstrual disorders, characteristics of the disorders, and factors influencing the risk of these disorders in different regions. Metabolomics was applied to analyze the characteristics of the salivary metabolites and neurotransmitters in the two groups of women with menstrual disorders. Results: The incidence rate of menstrual disorders was significantly higher in the H group than that in the C group (p < 0.05). High-temperature environment, stress, and sleep quality were identified as critical factors associated with menstrual disorders. Non-targeted saliva metabolomics identified 64 significantly different metabolites between two groups, which mainly enriched in metabolic pathways such as carbohydrate metabolism, membrane transport, digestive system, and nucleotide metabolism (p < 0.05). N-acetylneuraminic acid, MYO, and tyramine may be candidate markers for early diagnosis of menstrual disorders in high temperature environments. Metabolites may be involving in the acute-phase response during an inflammatory process, to affecting the reproductive system by influencing the HPA axis loop. Regulations about oocyte membrane production and the luteal functions would be exerted in menstrual disorders. Targeted metabolomics of neurotransmitters revealed increased expression of histamine (HA) and glutamine and decreased expression of 5-hydroxyindole acetic acid (5-HIAA) (p < 0.05). Conclusion: Menstrual disorder characteristics induced by high temperature environments were specific. Anxiety, sleep quality and temperature feeling were the key factors to the menstrual disorder. endocrine regulation mechanism and inflammatory reactions might contribute to the development of menstrual disorders through influencing the formation of the follicular cell membrane.